Associations between the number of antipsychotics prescribed and metabolic parameters in Japanese patients with schizophrenia. Issue 3 (7th July 2022) - Watanabe, Yuichiro; Ono, Shin; Sugai, Takuro; Suzuki, Yutaro; Yamazaki, Manabu; Sugawara, Norio; Yasui‐Furukori, Norio; Shimoda, Kazutaka; Mori, Takao; Ozeki, Yuji; Matsuda, Hiroshi; Okamoto, Kurefu; et al.
Abstract: Aim: There is little evidence on the effects of antipsychotic polypharmacy on metabolic parameters in patients with schizophrenia. Thus, this cross‐sectional study explored the associations between the number of antipsychotics prescribed and metabolic parameters in Japanese patients with schizophrenia. Methods: We obtained metabolic parameter data from 19, 675 patients with schizophrenia. Of these, 1380 (7.0%), 8422 (42.8%), 6326 (32.2%), and 3547 (18.0%) were treated with none, one, two, and three or more antipsychotics, respectively. We compared eight metabolic parameters among the four groups using univariate analyses. We then performed multiple regression analysis to assess the effect of the number of antipsychotics prescribed on metabolic parameters after controlling for the effects of age, sex, type of care (outpatient/inpatient), chlorpromazine‐equivalent dose, and antipsychotic type (aripiprazole, olanzapine, and risperidone). Results: There were significant differences in body mass index (BMI), systolic and diastolic blood pressure (dBP), total cholesterol, low‐density lipoprotein cholesterol, and triglycerides among the four groups. The multiple regression analysis showed that the number of antipsychotics prescribed was significantly correlated with BMI and dBP (standardized regression coefficient = 0.031 and 0.026, respectively). Conclusion: Our results suggested that the number of antipsychotics prescribed adversely affects BMI and dBP. Clinicians should avoid inappropriate antipsychotic polypharmacy, especially polypharmacy involving three or more antipsychotics. Abstract : Our results suggested that the number of antipsychotics prescribed adversely affects body mass index and diastolic blood pressure. Clinicians should avoid inappropriate antipsychotic polypharmacy, especially polypharmacy involving three or more antipsychotics.